The Implementation Of Clt In English Teaching - Learning Process At Sltp Negeri 2 Polokarto: An Ethnographic Approach - Waris. W, Dwi Kartika (2004)
The writer chooses the little of his research is the implementation of CLT in English teaching-learning process at SLTP Negeri 2 Polokarto: an ethnographic approach. The writer is interesting to observe of SLTP Negeri 2 Polokarto because the school is a new Junior High School in Polokarto. In this research, the writer wants to know the real implementation of CLT in English teaching-learning process at SLTP Negeri 2 Polokarto. The writer uses qualitative method and uses ethnographic approach because the study was related to the process. The writer gets data from informant. The informant is the English teacher who teaches English in the first class and in collecting the data, the writer uses the interview and observation. In analysing the data, the writer uses interactive model of analysis which has three component namely; (1) data reduction, (2) data display, and (3) conclusion. The writer finds two strategies in English teaching-learning process at SLTP Negeri 2 Polokarto. First, the strategy of code-mixing. Second, dictionary is used more in the classroom. The teacher and student roles in teaching-learning process at SLTP Negeri 2 Polokarto can be described that the students are receiver, processor and imitator in the classroom and the teacher is source of knowledge, a manager, a consultant in the classroom. The teacher had done her function as facilitator. The strength of CLT applied in SLTP Negeri 2 Polokarto is the students are active, relax in the classroom and they are brave to do communication using English. The weakness of CLT applied in SLTP Negeri 2 Polokarto is the students get a problem to use English sentences because influenced by Indonesian or Javanese language and teaching-learning process spends more energy and time. As a conclusion, the implementation of CLT in teaching learning process at SLTP Negeri 2 Polokarto is effective. The teacher had done her function as facilitator. she is active in supporting the students to express their ideas. So, She is successful in making students active in the classroom.